The Effectiveness of Mathematics Learning Using Online Media During the Covid-19 Pandemic - Nur'aini Muhassanah; Afifah Hayati; Ambar Winarni (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2022)
The Covid-19 pandemic has caused the learning process to be hampered and cannot be carried out face-to-face. Therefore, a solution is needed for this problem. One alternative to overcome this problem is online learning. This study aims to describe the effectiveness of online learning using online media during the Covid-19 pandemic in Mathematics courses. The subjects of this study were 51 students in the Faculty of Science and Technology, Nahdlatul Ulama University, Purwokerto. They were from five different study programs, namely Agrotechnology, Mathematics, Biology, Fisheries Science, and Agricultural Biosystems Engineering, who had taken mathematics courses. This study was carried out in June – August 2021. This study used closed, semi-closed, and open-ended questionnaires as research instruments. Then, the data collection procedure was done through Google Forms. The data obtained were then selected using purposive sampling. To get valid and reliable data, triangulation was applied in this study. Triangulation was carried out through interviews with five students whose data were selected randomly. The researchers used descriptive statistics as the data analysis. The study found that the activities most often carried out by students during Study From Home (SFH) are playing on cellphones or laptops, doing assignments, working, and sleeping. Then, related to online learning, students prefer to use WhatsApp Group media and lectures. The preferred assignments or assessments are individual assignments and quizzes. Furthermore, the learning model most favored by students is the face-to-face learning model because students consider online learning ineffective. The results of this study can be used as a reference in choosing the suitable model, method, and learning media. Therefore, online learning can be held effectively and easily accepted by students during the Covid-19 pandemic.